Link between Spot and Subsequent Closing Prices with Subsequent of Stock and Index in India - T, Vigneshwaran.; R, Srinivasan. (International Journal of Psychosocial Rehabilitation, 2019)
This research examines whether a relationship exists in India between spot and subsequent closing prices for NIFTY 50 stock and index subsequent on NSE. To achieve this objective, Nifty 50 Index & 25 select stocks are listed on the NIFTY 50 Index traded on NSE India for a period from April 2005 to December 2015, taking into account the inclusions and exclusions of the constituents of the Nifty 50 Index during the study period. The sample used in this study includes for Nifty Index & 25 select stocks traded on NSE (www.nseindia.com) daily subsequent close prices and spot closing prices. Since most trading activity occurs in near-month contracts, only near-month contracts are analyzed using econometric tools descriptive statistics, unit root check, granger causality, and correction of vector errors. The analysis reveals that spot-to-subsequent markets have a bidirectional relationship. The study also provides evidence of a long-run balance link between the index of spot market prices and their subsequent prices. This means that either of these two historic prices would help predict the other.